PENGARUH DISIPLIN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT PLN (UNIT INDUK PEMBANGUNAN SUMATERA BAGIAN UTARA) - Immanuel Maranatha Ginting; Try Aprina Bangun; Davin Veri Munthe; Sumiati Sihombing (JURNAL MANAJEMEN, 2019)
Employee performance plays an important role in increasing progress towards a better way to achieve company goals. Efforts to improve employee performance include looking at employee work discipline and communication. The purpose of this study was to determine the effect of discipline and communication on employee performance at PT. PLN Unit Induk Pembangunan Sumatera bagian Utara. The research method used a quantitative approach method. Data collection methods were done through interviews, questionnaires and documentation studies. The analytical method used multiple linear regression methods, coefficient of determination, simultaneous testing (F - test), and also partial testing (t - test). The results showed that simultaneously discipline and communication had a positive and significant effect on the performance of employees at the PT. PLN North Sumatra Development Main Unit. Partially, discipline and communication have a positive and significant effect on the performance of employees at PT PLN Unit Induk Pembangunan Sumatera bagian Utara.